2013
DOI: 10.1103/physrevlett.111.060803
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Boltzmann Constant by Means of Precision Measurements ofH2O18Line Shapes at1.39

Abstract: We report on a new implementation of Doppler broadening thermometry based on precision absorption spectroscopy by means of a pair of offset-frequency locked extended-cavity diode lasers at 1.39  μm. The method consists in the highly accurate observation of the shape of the 4(4,1)→4(4,0) line of the H2(18)O ν1+ν3 band, in a water vapor sample at thermodynamic equilibrium. A sophisticated and extremely refined spectral analysis procedure is adopted for the retrieval of the Doppler width as a function of the gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 24 publications
4
90
0
Order By: Relevance
“…These results are crucial from the point of view of recent very rapid developments of ultra-accurate spectroscopic measurements, where effective accuracy is no longer limited by experimental imperfections, but by the use of wrong line-shape models. 4,5,25 We showed that the BB model properly describes the velocity-changing collisions for H 2 -H 2 and H 2 -Ar. We did it by relating the results obtained from the BB model to those from ab initio CMDS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are crucial from the point of view of recent very rapid developments of ultra-accurate spectroscopic measurements, where effective accuracy is no longer limited by experimental imperfections, but by the use of wrong line-shape models. 4,5,25 We showed that the BB model properly describes the velocity-changing collisions for H 2 -H 2 and H 2 -Ar. We did it by relating the results obtained from the BB model to those from ab initio CMDS.…”
Section: Discussionmentioning
confidence: 99%
“…For other systems, well controlled quantification of these systematic errors will allow to increase the accuracy in many, recently rapidly developing, fields of optical metrology like spectroscopic determination of Boltzmann constant, where at the moment the main contribution to the error budget comes from oversimplified treatment of the spectral line shape. 4 The effective frequency of velocity-changing collisions…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations